2019
DOI: 10.1016/j.jmps.2018.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of contact location on the crushing strength of aggregates

Abstract: This work deals with the effect of the contact location distribution on the crushing of granular materials. At first, a simple drop weight experiment was designed in order to study the effect of the location of three contact edges on the fracture pattern and the strength of a model cylindrical particle. The sample was placed on two bottom contact edges symmetrically distributed with reference to the vertical symmetry plane of the particle and subjected to an impact at the top. Angle α between the plane connect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…Using drop weight crushing tests, Artoni et al [21] showed a strong effect of contact orientation on particle strength as well as similar fracture patterns.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Using drop weight crushing tests, Artoni et al [21] showed a strong effect of contact orientation on particle strength as well as similar fracture patterns.…”
Section: Introductionmentioning
confidence: 87%
“…From the review of experimental works, it should be noted that the coordination number was restricted to grains with a few coordination number less than or equal to 6 for Salami et al [10] and 4 for Artoni et al [21]. This restriction is not representative of particles that are part of a well graded granular assembly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decades, the particles generated for any granular assembly were simply circular or spherical; however, with the modern DEM, one can create a general particle shape using two or more circular or spherical particles [ 28 , 29 , 30 ]. The process of creating a particle of any shape is termed the clump or clustering method [ 27 ].…”
Section: Numerical Modelmentioning
confidence: 99%
“…In addition, the drop weight test (DWT) is widely used. DWT has been used to research the functional relationships between impact energy and crushed products and between contact location and fragmentation morphology [16,17].…”
Section: Introductionmentioning
confidence: 99%